Izzivi na poti zdravila od prihoda na trg do varnega in učinkovitega zdravljenja pacienta - Čebron Lipovec, Nanča (Farmacevtski vestnik, 2020)
Each medication receives marketing authorisation based on its proven safety and effectiveness in clinical trials. However, this is just the start of the path to the effective and safe patient treatment. After obtaining a marketing authorisation, the medication goes through the process of market uptake. The medication price is set, the reimbursement from public funds is determined and potential prescribing restrictions are specified. Once the medication is reimbursed and present on the Slovenian market, it becomes available to patients. However, the treatment instructions are often not understandable to patients. Particularly in chronic diseases, patients show poor adherence in medication therapy. Other medication related problems can also occur, such as side-effects or medication prescribing to different vulnerable populations, e.g. the elderly. Patient-related challenges are addressed and resolved by various pharmacy services, such as medication review and pharmacotherapy review. The path to effective and safe treatment is fraught with challenges, both at the system and patient level. These challenges are the central focus of research in the Chair of Social Pharmacy at the Faculty of Pharmacy, University of Ljubljana.
Keywords: dostop do zdravil; pismenost; pregled zdravil; socialna farmacija; sodelovanje; težave povezane z zdravili; vrednotenje zdravstvenih tehnologij; Zdravila